Single Phase Active Power Filter Control Under Distorted Grid Voltage Using Quasi Open-Loop Grid-Synchronization Technique - Biricik, Samet; Ahmed, Hafiz; Komurcugil, Hasan; Guler, Naki; Ozmen, Burcin; Benbouzid, Mohamed (IEEE, 2021)
This paper proposes a quasi open-loop gridsynchronization technique-based control scheme for active power filter. The proposed filtering technique does not require any direct frequency feedback which has the advantage of unconditional stability. Based on the reference a current, a proportional integral and hysteresis band current control scheme is developed for fast and accurate tracking of the reference current by the APF's converter. Matlab/Simulink-based extensive numerical simulation studies are performed to demonstrate the robust performance of the proposed technique in distorted grid.
12th Power Electronics, Drive Systems, and Technologies Conference (PEDSTC) -- FEB 02-04, 2021 -- Univ Tabriz, Fac Elect & Comp Engn, Tabriz, IRAN
Keywords: Active Power Filter; Grid-Synchronization; Adaptive Filtering